2018
DOI: 10.1039/c8an00130h
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of a biphasic, switch-like DNA amplification

Abstract: We report the first DNA amplification chemistry with switch-like characteristics: the chemistry is biphasic, with an expected initial phase followed by an unprecedented high gain burst of product oligonucleotide in a second phase. The first and second phases are separated by a temporary plateau, with the second phase producing 10 to 100 times more product than the first. The reaction is initiated when an oligonucleotide binds and opens a palindromic looped DNA template with two binding domains. Upon loop openi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Using reasonable parameter estimates based on values reported in the literature, we found that this model explains all key characteristics of the biphasic reaction described in [11]. Our model reproduces two distinct DNA amplification periods and two periods of stalled growth as observed in UDAR trials.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Using reasonable parameter estimates based on values reported in the literature, we found that this model explains all key characteristics of the biphasic reaction described in [11]. Our model reproduces two distinct DNA amplification periods and two periods of stalled growth as observed in UDAR trials.…”
Section: Introductionsupporting
confidence: 66%
“…The final parameters were chosen to fit the reaction initiation observed in experimental data for the template studied in this work while keeping reasonable values for the DNA association kinetics. The free energy of the trigger association to the looped template, given by the difference in free energy between the 3 0 toehold association with the trigger and the loop secondary structure, was one parameter shown in [11] to correlate with the inflection point of the first phase. This correlation is consistent across the biphasic amplification reactions originally reported.…”
Section: Parameter Rangesmentioning
confidence: 99%
See 3 more Smart Citations